EFFECT OF THREE ANTIBIOTICS ON BYPERIMENTAL INFECTION OF BROILERS WITH MYCOPLASMA GALLISEPTICUM - Abed, AH.; A. Alkhayyat, A.; N. Al-‎ Shammary, A. (The Iraqi Journal of Veterinary Medicine, 2024)
Four groups of 36 days old chicks were infected experimentally with mycoplasma ‎gallisepticun suspension while a control group was injected with nutrient broth and ‎another control group was left uninfected Thtee of the infected groups were treated with ‎either Tylosin Spiramycin or lincomycin.‎Parameters of airsacculitis score, and weight gain food conversion were used to evaluate ‎the treatment.‎Also, the residues of tylosin in blood plasm nd muscles and the level of spiramycin in blood ‎plasma was estimated by a microbiological assay.‎ The results showed significant differences between infected and non-infected ‎groups with all parameters used Treatment with tylosin and apramycin improved weight ‎gain and increased food consumption but did not reduce airsacculitis score. Tylosin level in ‎plasma was 75 μg/ml at termination of treatment and 0.16 μg/ml ‎ after 3 days, While ‎measurable level was seen after 7 days. With spiramycin the corresponding levele were ‎‎0.43, 0.20, and 0.18 μg/ml ‎ respectively. The level of tylosin in guacles was 0.14 μg/mg ‎